Building a Green Economy: The Role of Sustainable Energy in Saudi Arabia’s Economic Diversification under Vision 2030 - Sallam, Mohamed A. M.; Sadraoui, Tarek; Alwehaibi, Samar A. (International Journal of Energy Economics and Policy, 2025)
Saudi Arabia, long reliant on hydrocarbon revenues, faces mounting pressure to diversify its economy while meeting its climate commitments. This study examines the critical role of sustainable energy in enabling Saudi Arabia’s transition to a green economy under Vision 2030. Using a mixed- methods approach—combining policy analysis, renewable energy project data (2016-2023), and macroeconomic modeling—we assess how investments in solar, wind, and hydrogen contribute to economic diversification, job creation, and reductions in carbon emissions. Results indicate that renewable energy adoption could displace 12-18% of oil-derived electricity by 2030 while adding $15-20 billion annually to non-oil GDP. However, institutional barriers, fossil fuel subsidies, and technological gaps hinder progress. We propose targeted policy reforms, including public-private partnerships (PPPs) and localized supply chains, to accelerate green growth. This research underscores the synergy between energy sustainability and economic resilience, offering actionable insights for Saudi Arabia and other resource-dependent economies.